Towards Building a General Guideline Approach to Facilitate the Process of Measuring Software Usability. - A. Alferjani , Heba; A. Hagal , Mohamed (Libyan Journal of Science &Technology, 2026)
Usability and the extent of customers’ satisfaction with the applications that accomplish their work are important factors in facilitating their work procedures. For this reason, many criteria have been revealed that deal with the mechanism of usability. In addition to the attempts of many researchers to provide ways and methods to address and measure this feature, this was, in a way, generic or abstract, which causes many developers to neglect usability and not ad dress it primarily in the development stage. In this paper, we present a unified framework that addresses the elements of usability in a de tailed and organized manner, supported by a clear measurement method that includes a num ber of mathematical equations and guiding questions that facilitate this process for developers. A case study was presented as an applied example of the proposed framework, as it was clear from the target audience how simple it is to utilize this framework. Therefore, this framework can be considered as a supportive point to encourage developers to focus on usability more.